2009
DOI: 10.1016/j.actamat.2009.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of shear banding in compression of Zr41Ti14Cu12.5Ni10Be22.5 pillars as small as 150 nm in diameter

Abstract: Recently, the size dependence of mechanical behaviors, particularly the yield strength and plastic deformation mode, of bulk metallic glasses (BMG) has created a great deal of interest. Contradicting conclusions have been drawn by different research groups, based on various experiments on different BMG systems. Based on in situ compression transmission electron microscopy (TEM) experiments on Zr 41 Ti 14 Cu 12.5 Ni 10 Be 22.5 (Vit 1) nanopillars, this paper provides strong evidence that shear banding still pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…Both size-dependent [3,[7][8][9][10] and size-independent [12][13][14] shear banding behaviors in MG nanorods have been reported in experiments. Moreover, MD simulations on two-dimensional or threedimensional thin-slab geometry [15,16] show clear shear band formation, while MD simulations on three-dimensional nanowire samples show homogeneous flow [17,18].…”
mentioning
confidence: 99%
“…Both size-dependent [3,[7][8][9][10] and size-independent [12][13][14] shear banding behaviors in MG nanorods have been reported in experiments. Moreover, MD simulations on two-dimensional or threedimensional thin-slab geometry [15,16] show clear shear band formation, while MD simulations on three-dimensional nanowire samples show homogeneous flow [17,18].…”
mentioning
confidence: 99%
“…2,4,5 In addition to the atomic structure of the sample, shear band formation may also be influenced by extrinsic factors such as loading conditions, 6 microstructures 7 and the sample size. [8][9][10][11][12][13][14][15][16] Particularly, the size-dependent plasticity in MG systems has attracted considerable attention due to the advancement in micromechanical testing and sample preparation using focused-ion beam technique. Two related sizedependent plasticity have been investigated.…”
mentioning
confidence: 99%
“…2 Moreover, it was reported that shear bands could even be completely suppressed by reducing the sample size into the submicron scale, which led to a homogeneous deformation mode at room temperature. 3,4 However, the idea of the shear-band suppression is controversial and was later challenged by a few researchers based on their results of the microcompression experiments, [5][6][7] in which no homogeneous deformation mode was observed on the micropillars even though their diameters were reduced to a level less than that observed in the homogeneous deformation mode. It can be argued that the difference of the experimental results originates from the chemical composition of the microsamples, i.e., different BMGs have different critical length scales below which the shear bands cannot be nucleated.…”
mentioning
confidence: 99%
“…Thus, the homogeneous deformation is still an intrinsic effect, reflecting the shear-banding behavior at the small size scale. However, there is another extrinsic effect that could also cause the apparent deformation homogeneity, but was somehow ignored in previous studies, [2][3][4]6 which is derived from the sample geometry and the associated boundary conditions.In mechanical testing of single crystals, it is known that the grips play an important role in determining the deformation morphology of a tensile specimen. If the lateral translations of both grips are constrained, a dislocation single slip is not favored, and, thus, the resulting deformation morphology is a reflection of the combined effect of the sample geometry and dislocation dynamics.…”
mentioning
confidence: 99%
See 1 more Smart Citation